Organizational resilience and adaptive capacity: a case study in a family business in Rio Grande do Sul - Leite, Felipe Kopp; Cruz, Ana Paula Capuano da; D’Ávila, Lívia Castro; Walter, Silvana Anita; Silva, Francielle Molon da (Revista de Administração da UFSM, 2023)
Purpose: The study aimed to understand the dynamics of the relationship between organizational resilience and the adaptive capacity of a family company from Rio Grande do Sul, aiming to sustain its performance in the midst of the pandemic caused by the coronavirus. Design / methodology / approach: The research was operationalized by means of a case study, carried out in a family company in the food industry in the city of Pelotas, Rio Grande do Sul, Brazil. Data was collected by means of semi-structured interviews and document analysis. Afterwards, the material was transcribed and entered into NVivo® software to perform the content analysis. Findings: The results indicate that the resilience dimensions enabled the emergence of the company’s adaptive capacity to sustain itself amidst the turbulent environment. Therefore, the findings indicate that the organizational resilience of the company analyzed in this case study provided the company’s adaptation to the pandemic context through coping, recovery and resumption of the company in the face of change and uncertainty. Limitations / implications: We highlight the non-participation of the researchers effectively in the field, due to the restrictions imposed by the pandemic. This fact prevented the expansion of data triangulation through non-participant observation of the daily life of the family business. Practical implications: The study enables managers to reflect on how to sustain their companies in crisis environments through anticipatory or reactive actions, characterized based on dimensions of organizational resilience, which enable the company’s adaptive capacity. Originality / value: The originality of this study is confirmed by a bibliometric survey that found a lack of studies which use the approaches of organizational resilience, adaptive capacity, and perceived performance together, in the light of the socioemotional wealth theory.